Alginates modification and the prospective uses of their products. - Subaryono Subaryono (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2010)
Alginate is a natural hydrocolloid that is used in food and non food industries. The weakness ofnative alginate cause the limited uses of this material in industry. Some weaknesses of nativealginate had been successfully overcome either by the modification of alginate structure orinteraction of alginate with another substances. The low solubility of alginate and its low stabilityagainst acid had been successfully resolved with esterification of alginate backbone with propyleneglycol, producing propylene glycol alginate (PGA). The high syneresis of alginate gel had beensuccessfully overcome with partial hydrolysis, producing short chain alginate, introduce shortchain polyguluronate and interact alginate with other substances such as locust bean gum (LBG).Alginate hydrophilic properties could be changed into amphiphilic by long alkyl chain substitutiontowards part of the polysaccharides group. The ability of alginate to promote the growth of probioticbacteria could be done by enzymatic hydrolysis of alginate using alginate lyase producingalginate oligosaccharides (AOS). The modification of alginate had opened the big opportunity forthe uses of alginate and its derivatives, both in food and non food sectors.